Investigation into the impacts of rock/cutter interface geometry on drilling response of PDC cutters - Doshvarpassand, Siavash (Curtin University, 2017)
This thesis investigates the effects of geometry on the cutting action of circular sharp PDC cutters. Results of extensive laboratory rock cutting experiments indicate that the force acting a cutter while tracing a groove is affected by the geometry or shape of the groove and in particular: (a) the length of the cutter edge in contact with the rock, and (b) the relative section of rock material located above the cord of the groove.